Pengaruh Intellectual Capital dan konservatisme Akuntansi Terhadap Kinerja Keuangan - Sulistyawati, Iin; Susilo, Dwi Ermayanti (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
In the era of globalization, economic growth has a huge impact on companies in Indonesia. Under these conditions, companies must openly present information that describes financial performance. This research was conducted to determine the influence of Intellectual capital and accounting conservatism on financial performance. The research design uses quantitative methods with time series data for 2019-2022. The data analysis technique used is multiple linear regression analysis. The data source for this research comes from 18 oil and gas companies listed on the Indonesia Stock Exchange (BEI). The sampling technique in this research was purposive sampling method, data was obtained from 15 companies. The research results show that intellectual capital has an effect on financial performance and accounting conservatism has no effect on financial performance.